Exploring social ecological pathways from resilience to quality of life among women living with HIV in Canada. (23rd August 2018) - Logie, Carmen H.; Wang, Ying; Kazemi, Mina; Hawa, Roula; Kaida, Angela; Conway, Tracey; Webster, Kath; de Pokomandy, Alexandra; Loutfy, Mona; ,
ABSTRACT: Resilience, positive growth in contexts of stress and adversity, is shaped by social ecological factors. Among people living with HIV, resilience is associated with myriad positive health benefits and improved health-related quality of life (HR-QoL). Identifying contextual factors associated with resilience among women living with HIV (WLWH) is particularly important as this population experiences many stressors and inequalities. We examined social-ecological factors associated with resilience and its relationship with HR-QoL among WLWH. We utilized baseline survey data from a national cohort of WLWH ( n  = 1424) in Canada. We conducted structural equation modelling using maximum likelihood estimation methods to test the direct effects of social support and women-centred HIV care (WCHC) on resilience, and the direct effects of resilience on mental and physical HR-QoL. We also tested the indirect effects of resilience on HR-QoL via HIV disclosure concerns and economic insecurity. Participant median age was 43 years (IQR = 35–50); most participants were women of colour (29% Black; 22% Indigenous; 7% other ethnicities; 41% Caucasian). Social support and WCHC were associated with increased resilience. The direct path from resilience to mental HR-QoL was significant, accounting for the mediation effects of economic insecurity and social support. The direct path from resilience to physical HR-QoL was significant, accounting for the mediation effects of economic insecurity. Economic insecurity partially mediated the relationship between resilience and mental HR-QoL and physical HR-QoL. HIV disclosure concerns partially mediated the relationship between resilience and mental-HR-QoL. Model fit indices suggested that the model fit the data well ( χ 2[14] = 160.378, P  < 0.001; CFI = 0.987; RMSE = 0.048 [90% CI:0.042–0.080]; SRMR = 0.036). Findings suggest social (social support) and structural (WCHC) factors increase resilience. While resilience is associated with improved HR-QoL, social (HIV disclosure concerns) and structural (economic insecurity) factors partially mediate these associations and threaten HR-QoL. Multi-level interventions can address social ecological contexts to advance resilience and HR-QoL among WLWH.